2020
DOI: 10.3389/fneur.2019.01408
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Study of the Intra-Neuroendoscopic Technique for the Treatment of Subacute-Chronic and Chronic Septal Subdural Hematoma

Abstract: The surgical technique, safety, efficacy, and clinical application value of the intra-neuroendoscopic technique (INET) for the treatment of subacute-chronic and chronic septal subdural hematoma was investigated based on the structure and pathological features of the hematoma wall, and the critical factors of hematoma growth and recurrence were determined, in order to provide reference for clinical drug treatment. Methods: This was non-randomized concurrent control study. A total of 94 patients who met the incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
0
11
0
2
Order By: Relevance
“…The authors showed that men probably had more trauma and more frequent complications than women. In addition, brain atrophy of older patients may contribute to the development of CSDH [ 20 ]. In the present study, gender, age, and history of head trauma were shown to be non-significantly associated with postoperative recurrence, as well as in the past history, such as a history of disturbed liver function, heart disease, malignant tumor, diabetes, hemodialysis, coagulopathy, and alcoholism ( p > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The authors showed that men probably had more trauma and more frequent complications than women. In addition, brain atrophy of older patients may contribute to the development of CSDH [ 20 ]. In the present study, gender, age, and history of head trauma were shown to be non-significantly associated with postoperative recurrence, as well as in the past history, such as a history of disturbed liver function, heart disease, malignant tumor, diabetes, hemodialysis, coagulopathy, and alcoholism ( p > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The follow-up time in four studies was quite different. In the studies by Du et al ( 12 ); Zhang et al ( 16 ), the follow-up time was 6 months, and the follow-up time was 12 months in the study by Yan. The results in these three studies are comparable.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies have remained, and their full texts were acquired for assessing their eligibility. Finally, seven single-arm studies were excluded, and four studies were eligible and included in meta-analysis (12)(13)(14)(15). To our dismay, no RCTs were included.…”
Section: Study Selectionmentioning
confidence: 99%
“…Recently, endoscopic hematoma evacuation was introduced for coagulated hematoma, multiple septal membranes in the hematoma, and recurrent CSDH. [35][36][37] The first endoscopic treatment for CSDH was described by Karakhan in 1988. 38) Since that paper, several studies have reported the safe management of CSDH by endoscopic surgery.…”
Section: Fig 2 Historical Review Of Reports From Around the World Reg...mentioning
confidence: 99%